Sistem Pengolahan Air Limbah Elektroplating Berbasis Nikel - Galu Murdikaningrum; Djaenudin Djaenudin; Kenny Kencanawati; Wendi Hermawan (Universitas Insan Cendekia Mandiri, 2019)
In line with industrial development and scientific and technological advancement, the use of metals cannot be separated from human life. Aside from benefits, the rapidly increasing industrial developments also give negative impact from their heavy metal waste. Some electroplating waste treatment methods are studied in this research, specifically electrodeposition method, electrocoagulation, and pH 9 hydroxide coagulation method. This research aimed to determine the most effective method and conditions from the 3 methods mentioned above in reducing contents of nickel in the wastewater. The artificial wastewater was made to have the same concentration to waste from electroplating industry; specifically 2154.20 mg/L. The most effective reduction of nickel for this method occurs at 6 volts with final concentration of 404.86 mg/L. The treatment result from electrodeposition was then further processed through two different processes, a electrocoagulation method and pH 9 hydroxide coagulation method. Electrocoagulation process was done for 1 hour with variation in voltage at 5; 7, 5; and 10 volts. Metal Al was used at the anode, while metal Cu was at the cathode. The optimum voltage for this process occurs at 10 volts with final concentration of nickel at 164,98 mg/L, nickel elimination efficiency was at 59.25 %, specific energy at 1.0777 kWh/kg and current efficiency at 32.3 %. Sample from electrodeposition which was processed further with pH 9 coagulation process produced final nickel concentration at 25.59 mg/L, nickel elimination efficiency was at 93.68 %. Keywords: electrocoagulation; electrodeposition; electroplating; hydroxide coagulation; nickel.